Life and Death in One Breath - Sadhguru (Jaico Publishing House, 2013)
"Death is a cosmic joke. If you get the joke, when you fall on the other side, it will be wonderful. If you don't get the joke, when you are here you fear the other side, and when the other side comes, you just don't know what it is about. If death becomes a laughing matter in your life, life becomes an utterly effortless process - there is no need.